Effect of feeding Bacillus subtilis on rumen fermentation, blood metabolites, nutrient digestibility, and energy and nitrogen balances in non‐lactating crossbred cows. (26th February 2021) - Kawauchi, Daisuke; Angthong, Wanna; Keaokliang, Ornvimol; Ishida, Tetsuya; Takahashi, Toshihiro; Kawashima, Tomoyuki
Abstract: The purpose of this study was to investigate the effects of feeding Bacillus subtilis on rumen fermentation, blood metabolites, nutrient digestibility, and energy and nitrogen balances in non‐lactating crossbred (Holstein‐Friesian × Bos indicus ) cows. Four cows were assigned to the control and B. subtilis diets in a crossover design, and respiratory and metabolic experiments were conducted. For the B. subtilis diet, B. subtilis DSM15544 spores were added at the rate of 1.0 × 10 10 CFU/head/day to the control diet. At 4 hr after feeding, cows fed the B. subtilis diet had increased levels of i‐butyric acid in the rumen fluid and tended to have lower concentrations of plasma non‐esterified fatty acids when compared with cows fed the control diet. This suggests that feeding B. subtilis could improve energy efficiency. However, there was no effect on energy retention in this study. Although there were no effects on nutrient digestibility, nitrogen balance, or methane production, heat production was significantly higher in cows fed the B. subtilis diet than in those fed the control diet.